Letters from the Past - Naksyl, Herel M. (The New Research of Tuva, 2010)
Pondering a question “How the railroad will change life in Tuva?”. Winner in “The dialogue of generations” nomination.
Keywords: konkurs; Tuva-2050; foresight; youth; essay